Russia under western eyes : from the Bronze Horseman to the Lenin Mausoleum - Malia, Martin E. (Martin Edward) (Cambridge, MA : Belknap Press of Harvard University Press, 1999)
"This is not a book about Russia as such; it is a book about Europe as a whole, offering an original perspective that reconceptualizes Western history. Here modern Europe is depicted as a West-East cultural gradient in which the central and eastern portions respond to the Atlantic West's challenge in delayed and generally skewed fashion. Thus Russia, after two centuries of building then painfully liberalizing its Old Regime, in 1917 tried to leap to a "socialism" that would be more advanced and democratic than European "capitalism." The result was a cruel caricature of European civilization, which mesmerized and polarized the West for most of the twentieth century. As the old West-East gradient reappears in genuinely modern guise, this brilliantly imaginative work shows us the reality that has for so long tantalized - and eluded - Western eyes."--Jacket
Introduction: The Russian riddle -- Russia as enlightened despotism: 1700-1815 -- Russia as oriental despotism: 1815-1855 -- Russia as Europe regained: 1855-1914 -- War and revolution: 1914-1917 -- Through the Soviet-Russian looking-glass, and what the west found there: 1917-1991 -- Conclusion.
Includes bibliographical references (pages 437-482) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Russia (Federation) -- Civilization; Soviet Union -- Civilization; Russia (Federation) -- Foreign public opinion; Soviet Union -- Foreign public opinion; Russia (Federation) -- History; Soviet Union -- History; URSS -- Civilisation; URSS -- Histoire; HISTORY; HISTORY -- Europe -- Russia & the Former Soviet Union; Civilization; Public opinion; Russia (Federation); Soviet Union; Beeldvorming; Electronic books; History